The World and God Are Not-Two: A Hindu–Christian Conversation - Soars, Daniel (Comparative Theology: Thinking Across Traditions, 2023)
The World and God Are Not-Two is a book about how the God in whom Christians believe ought to be understood. The key conceptual argument that runs throughout is that the distinctive relation between the world and God in Christian theology is best understood as a non-dualistic one. The “two”—“God” and “World” cannot be added up as separate, enumerable realities or contrasted with each other against some common background because God does not belong in any category and creatures are ontologically constituted by their relation to the Creator.In exploring the unique character of this distinctive relation, Soars turns to Sara Grant’s work on the Hindu tradition of Advaita Vedānta and the metaphysics of creation found in Thomas Aquinas. He develops Grant’s work and that of the earlier Calcutta School by drawing explicit attention to the Neoplatonic themes in Aquinas that provide some of the most fruitful areas for comparative engagement with Vedānta. To the Christian, the fact that the world exists only as dependent on God means that “world” and “God” must be ontologically distinct because God’s existence does not depend on the world. To the Advaitin, this simultaneously means that “World” and “God” cannot be ontologically separate either. The language of non-duality allows us to see that both positions can be held coherently together without entailing any contradiction or disagreement at the level of fundamental ontology. What it means to be “world” does not and cannot exclude what it means to be “God.”